Is the relationship between sedentary behaviour and cardiometabolic health in adolescents independent of dietary intake? A systematic review. Issue 9 (22nd June 2015) - Fletcher, E.; Leech, R.; McNaughton, S. A.; Dunstan, D. W.; Lacy, K. E.; Salmon, J.
Summary Screen time, but not overall sedentary behaviour, is consistently related to cardiometabolic health in adolescents. Because of the associations screen time has with dietary intake, diet may be an important factor in the screen time and health relationship; however, evidence has not previously been synthesized. Thus, the aim of this systematic review was to explore whether the associations between various sedentary behaviours and cardiometabolic risk markers are independent of dietary intake in adolescents. Online databases and personal libraries were searched for peer‐reviewed original research articles published in English before March 2014. Included studies assessed associations between sedentary behaviour and cardiometabolic markers in 12‐ to 18‐year‐olds and adjusted for dietary intake. Twenty‐five studies met the inclusion criteria. From the 21 studies examining sedentary behaviour and adiposity, the majority found significant positive associations between television viewing, screen time and self‐reported overall sedentary behaviour with markers of adiposity, independent of dietary intake. No significant associations between screen time with blood pressure and cholesterol were reported. Sedentary behaviour appears to be associated with adiposity in adolescents, irrespective of dietary intake. However, the variability of dietary variables between studies suggests further work is needed to understand the role of dietary intake when examining these associations in youth.